PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN - Abdul Rohim (Ekonis: Jurnal Ekonomi dan Bisnis, 2018)
The purpose of this study was to determine whether there is positive work environment on job satisfaction, to determine whether there is positive work environment on employee performance, to determine whether there is a positive effect of job satisfaction on employee performance, to determine whether there is influence of the working environment on performance employees through job satisfaction. Primary data types, methods of collecting data through observation, interviews and questionnaires. The population used in this research is the production employees Djombang New Sugar Factory class IA-IID as many as 180 employees. The sampling technique purposive sampling method. Analysis of data to test the hypothesis in this study using path analysis (Path analys). Based on the analysis and discussion can be concluded that there is a significant positive effect on job satisfaction working environment it shows that the higher the working environment, the higher employee satisfaction. There is a significant positive effect on employee performance work environment means that any increase in the working environment, the performance of employees will increase. There is a significant positive effect of job satisfaction on employee performance means that any increase in job satisfaction of the employee's performance will increase. There is no direct influence on employee performance work environment through job satisfaction. The higher the working environment will result in the higher the satisfaction, and indirectly will result in the higher the performance. Keywords: Work environment, job satisfaction, employee performance